Carbon Neutrality Policies and Technologies: A Scientometric Analysis of Social Science Disciplines - Zhang, Yuan; Pan, Chung-Lien; Liao, Han-Teng (Frontiers in Environmental Science, 2021)
Carbon neutrality, or “net zero”, has become the impact assessment project of human impact on earth, increasingly structured to examine the implications, for the environment and people, of proposed actions and consequences of inaction. International and local collaboration efforts have been made with the aim of achieving carbon neutrality or "net-zero" emissions; thus, policies and technological innovations have been developed. Such impact-oriented risk assessment and control efforts amount to carbon-neutral pathways. Although such pathways may diverge in terms of energy, resources, and cost, it is critical to summarize essential and promising preparatory work on related policies and technologies to inform both policy-makers and social scientists to take actions. Through a scientometric analysis and scoping review of the latest social science literature, the study identified the size, scope and exemplar work for each social science discipline on carbon neutrality, based on 907 articles collected in early 2021 from the Web of Science database. This study reveals a set of disciplines focusing on certain common and distinct aspects of carbon neutrality. By outlining the possibilities and application areas for future research and policy development for socio-technical transition towards a net-zero or post-carbon future, this study has contributed to the understanding of the global efforts to achieve a clearer and viable carbon-neutral pathway. In conclusion, as many aspects of the planet and humans have become datafied, digitized, and networked, carbon neutrality, as the ecological indicator that guide human production and consumption patterns, must take on a central role in guiding our conscious green digital transformation of many political, economic, social and psychological aspects of our societies according to the existing and emerging social science knowledge.